Linguistic Analysis of the Two Speech Functions in President Donald Trump’s Inaugural Speech - Tchaparian, Vicky (Armenian Folia Anglistika, 2017)
The purpose of this study is the linguistic interpretation of President Donald Trump’s inaugural speech during the ceremony held in Washington D. C. on January 21, 2017. The two functions of speech which will be analyzed here are the grammatical and textual functions. The findings reveal two main themes: one is the criticism of the economic situation of America during the last years and the other is a promise and a vow for a change towards a better future where the economy will flourish and there will be prosperity. The study shows the president’s determination to make America strong again, safe again, and prosperous again.